Biomarkers for diagnosis of pre-eclampsia and endometriosis. (7th September 2018) - Wahid, Braira; Rafique, Shazia; Ali, Amjad; Waqar, Muhammad; Nabi, Ghulam; Wasim, Muhammad; Idrees, Muhammad
Gynecological disorders are leading public health problems in developing countries with substantial impact on women's quality of life. Significant proportion of maternal mortality and reproductive morbidity is attributed to misdiagnosis and mismanagement of pregnancy related lethal pathological conditions and affect women's health. Timely diagnosis is necessary to prevent maternal deaths and to manage complications. Biomarker development will create a wide window of opportunity for early diagnosis. This review discusses the current status of biomarkers and recent advances in 'omics' technology for early screening of endometriosis and pre-eclampsia because of significant global bioburden associated with these disorders. This review will also give baseline data for future biomarker development strategies.